2000
DOI: 10.4049/jimmunol.165.1.364
|View full text |Cite
|
Sign up to set email alerts
|

IL-4-Independent Inhibition of IL-12 Responsiveness DuringLeishmania amazonensisInfection

Abstract: Leishmania amazonensis induces a nonhealing infection in C3H mice, whereas infection with Leishmania major is self-healing. We found that C3H mice infected with L. amazonensis exhibited decreased IL-12 production, which could account for the susceptibility to this organism. However, exogenous IL-12 administration failed to induce a healing immune response. The failure of L. amazonensis-infected C3H mice to respond to IL-12 was associated with a specific defect in IL-12 receptor β2 (IL-12Rβ2) mRNA expression by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
139
2
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(150 citation statements)
references
References 59 publications
(40 reference statements)
8
139
2
1
Order By: Relevance
“…Resolution of L. major in genetically resistant mice is ascribed to a polarized Th1 immune response, while the susceptibility in BALB/c mice is attributable to selective expansion of Th2 cells (Sacks and Noben-Trauth, 2002). However, we and others have found that La infection results in nonhealing disease in most inbred mouse strains due to the induction of a weak, Th1/Th2 mixed response (Ji et al, 2002;Jones et al, 2000). The deficient Th1 response seen in La-infected mice is due largely to profound, multiple impairments in numerous cytokines, chemokines, and their corresponding receptors at an early stage of the infection (Ji et al, 2003).…”
Section: Introductionmentioning
confidence: 84%
“…Resolution of L. major in genetically resistant mice is ascribed to a polarized Th1 immune response, while the susceptibility in BALB/c mice is attributable to selective expansion of Th2 cells (Sacks and Noben-Trauth, 2002). However, we and others have found that La infection results in nonhealing disease in most inbred mouse strains due to the induction of a weak, Th1/Th2 mixed response (Ji et al, 2002;Jones et al, 2000). The deficient Th1 response seen in La-infected mice is due largely to profound, multiple impairments in numerous cytokines, chemokines, and their corresponding receptors at an early stage of the infection (Ji et al, 2003).…”
Section: Introductionmentioning
confidence: 84%
“…Whereas a majority of inbred mouse strains develop self-healing lesions when infected s.c. with L. major, virtually all mice develop rapidly growing large nonhealing lesions full of parasites following s.c. L. mexicana infection (40,41). BALB/c mice are an exception in that both parasites cause progressive disease (3,4,40,41).…”
Section: Discussionmentioning
confidence: 99%
“…1 and 3) However, the contribution of type 2 cytokines to progressive infection with other Leishmania species is variable. For instance, during L. chagasi infection the type 1 response is inhibited by TGF-␤ (42), whereas type 1 immunity is inhibited by other non-IL-4 factors during infection with L. mexicana and Leishmania donovani (4,43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations